Gender Workshop Nairobi Kenya 22-25 October - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On 22-25 October, CCAFS theme Linking Knowledge to Action organised a Gender Workshop for researchers and development practitioners working in the field of gender and climate change. The workshop brought up issues related to conducting research on gender and creating and implementing gender strategies. Photos: C. Schubert (CCAFS)